EFFECT OF CANDLENUT SHELL ASH AS A SAND SUBSTITUTION ON COMPRESSIVE STRENGH OF PAVING BLOCK - Luqman Cahyono; Yulia Riska Dwi Sinta; Nabillah Rodhifatul Jannah; Inas Aidah Fikriyah; Putri Nabiilah Anwar; Desita Romadona Syah Putri; Agung Prasetyo Utomo (LPPM Universitas Negeri Jakarta, 2023)
Candlenut is a superior commodity with great opportunities. Processing of candlenut seeds produces candlenut shells which are hard with a calorific value of 4164 cal/g so can be used as fuel. Processing candlenut shells as fuel produces waste of ash and not been utilized optimally. In this research, candlenut shell ash was used as a new alternative in making paving blocks, namely to substitute sand by 13%, 18% and 25% by weight of sand. The method used to analyze the chemical content of candlenut shell ash through XRF testing and compressive strength testing with a Compression Testing Machine after 28 days of curing time. Based on the results of the XRF test, hazelnut shell ash has a CaO content of 93.3%, where CaO is the main ingredient for making cement. In addition, the results of the average compressive strength of paving blocks at 13% substitution of candlenut shell ash produced a compressive strength of 5.89 Mpa, 18% substitution of candlenut shell ash of 8.72 Mpa, and 25% substitution of candlenut shell ash of 11.07 Mpa. The results of the compressive strength of paving blocks with the substitution of hazelnut shell ash produced standard standard paving block strength of D quality.